Neurotic styles - Shapiro, David 1926- (The Austen Riggs Center. Monograph series, 1965)
An original, clinical study of four kinds of neuroses--obsessive-compulsive, paranoid, hysterical and impulsive--and of the special characteristics of each. The author first reviews significant theoretical and research contributions to the psychology of character. Then, drawing on his own extensive clinical observation, he examines in close detail the ways of thinking and perceiving, forms of emotional experience, modes of activity, and behavioral manifestations--the "styles--that characterize these four kinds of neuroses. In conclusion he explores, in the light of these studies, some basic questions concerning the origin and development of styles--how their development is influenced by instinctual drives, their possible significance for drive-tension control and regulation, and their relationship to defense mechanisms.